A study of hearing loss in infants using brain stem evoked response audiometry - Polisetti, Ravibabu; Lanke, Sowmya; Vanipenta, Teja (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Background: Hearing is necessary to learn languages and speech and to develop cognitive skills. Unfortunately, many children with severe hearing loss from birth are not diagnosed until 21/2-3 years. of age. Implementing high-risk neonatal screening, detecting hearing loss before 3 months, and intervention before 6 months will result in a better speech performance of neonates. Methods: Detailed history taking and general and ear, nose and throat (ENT) examination were done to rule out external ear and middle ear pathology. Brainstem evoked response audiometry (BERA) was done in a dust-free, sound-proof, airconditioned room. Feed was given 10–15 min before the procedure. Syrup pedichloryl 20 mg/kg was given to sedate the baby half an hour before the procedure. Intelligent hearing system BERA instrument was used. The study included a total of 60 infants. 30 were in the high-risk group and 30 were in the normal group. There were 14 males and 16 females in each group. Results: 21 infants had hearing loss out of the 30 infants in the high-risk group on initial screening. On doing a repeat BERA after 3 mins on the affected infants, 3 were detected to have normal hearing, i.e., 18 out of 30 infants were affected. All the infants in the normal or no risk factor group had normal hearing. Conclusions: The present study emphasizes the importance of using ABR as a screening tool for the detection of hearing impairment at an early stage which would have otherwise go unnoticed for about 2-3 years. Since it is an objective test, it is useful in the early identification of hearing loss.